The content of a training package in diagnostic ultrasound for physiotherapists. Issue 1 (March 2015) - McKiernan, Sharmaine; Chiarelli, Pauline; Warren‐Forward, Helen
Abstract: Introduction: In recent years, the use of diagnostic ultrasound has expanded into the physiotherapy profession; however, training in the use of the modality is limited. It is widely accepted that ultrasound imaging is a user‐dependent modality, so without training, physiotherapists are likely to struggle with its use within their profession. The purpose of this study is to report on the content of a training package for physiotherapists in diagnostic ultrasound. Method: Physiotherapists training needs were previously explored using focus groups and a national survey. Insight gained was then used to develop a training package to cover the basic theory of ultrasound and scanning of the abdominal muscles, multifidus and pelvic floor. A combination of lectures, practical scanning sessions and image interpretation was used to deliver the curriculum. Results: The training package was developed to be delivered flexibly using two methods: workshop and DVD. The same content was covered in both formats with recorded lectures, video footage and cine clips used on the DVD to replace the live content of the workshop. Discussion: A training package in diagnostic ultrasound for physiotherapists was developed, and from participant feedback, the content can be said to have improved participant knowledge and confidence when using diagnostic ultrasound. © 2015 Australasian Sonographers Association